2016
DOI: 10.1021/acs.analchem.6b02821
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Time-of-Flight/Time-of-Flight Events in a Single Laser Shot for Improved Matrix-Assisted Laser Desorption/Ionization Tandem Mass Spectrometry Quantification

Abstract: Quantitative matrix-assisted laser desorption/ionization time-of-flight (MALDI TOF) approaches have historically suffered from poor accuracy and precision mainly due to the nonuniform distribution of matrix and analyte across the target surface, matrix interferences, and ionization suppression. Tandem mass spectrometry (MS/MS) can be used to ensure chemical specificity as well as improve signal-to-noise ratios by eliminating interferences from chemical noise, alleviating some concerns about dynamic range. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 53 publications
1
9
0
Order By: Relevance
“…Therefore, it is a feasible method to quantitatively describe the relative exposure level of BAs in tissue sections by the average intensity ratio of each BA to NPA. Two of the major impediments to the application of MALDI to quantitative experiments are signal suppression and signal interference, especially, of less concentrated components ( 24 ). However, this effect can be compensated for the use of an IS and optimization of the experimental parameters ( 24 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is a feasible method to quantitatively describe the relative exposure level of BAs in tissue sections by the average intensity ratio of each BA to NPA. Two of the major impediments to the application of MALDI to quantitative experiments are signal suppression and signal interference, especially, of less concentrated components ( 24 ). However, this effect can be compensated for the use of an IS and optimization of the experimental parameters ( 24 ).…”
Section: Resultsmentioning
confidence: 99%
“…Two of the major impediments to the application of MALDI to quantitative experiments are signal suppression and signal interference, especially, of less concentrated components ( 24 ). However, this effect can be compensated for the use of an IS and optimization of the experimental parameters ( 24 ). NPA, chemically different from BAs, has been proved to be effective in quantifying BAs directly from plasma and urine by MALDI-TOF-MS ( 22 , 23 ).…”
Section: Resultsmentioning
confidence: 99%
“…The LOQ for enalapril in this assay is 0.0960 μg/ml, which is within the therapeutic range of enalapril in plasma samples. 50,51 Although it has already been demonstrated that internal standard normalization improves the accuracy, precision, and linearity of the MALDI quantification assays, 40,52 effecting multiple isolation windows using multi-CASI allows for the novel sequential isolation of an analyte and internal standard pair that are disparate in mass-to-charge ratio. This method is broadly applicable to instruments that possess a QMF for isolating the ions of interest and a downstream ion trap that can store the ion population generated from each portion of the laser shots before mass analysis, such as many Oribtrap and Q-TOF platforms.…”
Section: Quantification Using Multiple Mass Isolation Windowsmentioning
confidence: 99%
“…Additionally, this approach can be used for the simultaneous analysis of multiple compounds over a broad mass range. Prentice et al 40,41 demonstrated this approach on a TOF/TOF platform by using a pulsed voltage gate to selectively transmit ions based on flight time. Multiple mass windows have also been employed on quadrupole ion traps and QMFs by applying broadband dipolar alternating current (AC) isolation waveforms that contain multiple frequency notches matched with the secular frequencies of ions of interest 42,43 …”
Section: Introductionmentioning
confidence: 99%
“…MALDI imaging has been combined with tandem mass spectrometry for improved selectivity in compound identification. 5,7,8 MALDI TOF/TOF instruments have the advantage of high data acquisition rate and large mass range, [9][10][11][12][13] but other instruments such as triple quadrupole 14 and hybrid quadrupole time of flight, 15,16 and quadrupole ion trap instruments have been used. 17 High-resolution Fourier transform ion cyclotron resonance 18 and Orbitrap sacrifice some scan speed but have high value in compound identification.…”
Section: Introductionmentioning
confidence: 99%